DETERMINANTS OF PURCHASE DECISION-MAKING OF HYPERTENSIVE MEDICINE (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
This study investigates the key determinants influencing the purchase of hypertension medication. This study involved 100 hypertensive patients in Yogyakarta who purchased hypertension medication. Data were collected using a validated and reliable research questionnaire. Multiple regression analysis was used to test the hypotheses. The results of this study indicate that (1) price perception has a positive effect on the purchase of hypertension medication, as evidenced by a significance value of 0.011, less than 0.05; (2) promotion has a positive effect on intention to purchase hypertension medication, as evidenced by a significance value of 0.002, less than 0.05; and (3) product quality has a positive effect on repurchase intention. The implication is that pharmaceutical companies set appropriate prices to compete with other pharmaceutical companies, increase promotion of hypertension medication, and maintain and improve the quality of hypertension medication that patients trust so that they continue to repurchase the medication and avoid switching to other brands.
Keywords: Price; Promotion; Quality; Purchasing; Hypertensive